Effect of hydroxyapatite and 45S5 bioactive glass addition on a dental adhesive resin cement - da Costa Lima Assad, Julia Magalhães; Ferreti Bonan Dantas Batista, Roberta; Anami, Lilian Costa; Almeida, Amanda [UNESP]; de Araújo Ferreira Muniz, Isis; de Melo Marinho, Renata Marques [UNESP]; Dantas Batista, André Ulisses; Cançado Castellano, Lúcio Roberto; Ferreti Bonan, Paulo Rogério (Wiley, 2021)
Objective: This study evaluates the mechanical, physical, and biological properties of resin-based dental cement (RelyX ARC, 3M ESPE) incorporated with hydroxyapatite and 45S5 bioactive glass. Methods: Bioactive glass (45S5) and hydroxyapatite (HA) were added to cement in different proportions (10 wt% and 20 wt%). Three-point flexural strength, microhardness, surface roughness, film thickness, contact angle, and color were evaluated. Cytotoxicity in human osteoblasts culture (MG63) was evaluated. Statistical analysis was performed using one-way and two-way ANOVA and Tukey tests (α < 0.05). Results: The addition of HA and 45S5 bioactive glass reduced the flexural strength of the composite. However, the resistance value was greater than the minimum values of the ISO standard. Film thickness was below the maximum values, except for the 20% HA. The contact angle was constant at 24 hours and 14 days, except for 10% 45S5 group, which presented a significant decrease in mean contact angle. Cellular viability for all groups increased from the first to the 14th day. Additionally, the cellular viability was above 50%. Conclusions: In vitro incorporation of 45S5 bioactive glass on resin cement resulted in a promising luting dental material with adequate mechanical properties, thin film thickness, improved wettability, and adequate biocompatibility.
Keywords: bioglass 45S5; biomedical applications; hydroxyapatites; mechanical properties; resin cement